Associations of breastfeeding duration and cognitive development from childhood to middle adolescence - Lovcevic, Irena (My University, 2023)
Aim To assess the dose-response association between the duration of any breastfeeding and cognitive skills in children from 5 to 15 years of age. Methods The data from the longitudinal cohort study Growing up in Australia: The Longitudinal Study of Australian Children (children born in 1999 – 2000 and 2003 – 2004) were accessed. Language skills were assessed via Peabody Picture Vocabulary Test at 5, 7, and 9 years of age (N = 8643), non-verbal intelligence was assessed via Matrix Reasoning subtest from Wechsler Intelligence Scale at 7, 9, and 11 years of age (N = 8560), and executive functions were examined via Cogstate Cognitive Testing battery in 15-year-old (N = 6213). Breastfeeding was assessed via maternal questionnaires, partly prospective. Results A longer duration of breastfeeding was significantly associated with greater language skills from 5 to 9 (0.05 [95 % CI, 0.04 to 0.06], p < .001) and greater non-verbal intelligence from 7 to 11 years of age (0.02 ([95 % CI, 0.01 to 0.02], p < .001). No significant relation was found between the breastfeeding duration and executive functions in 15-year-old. Conclusion These results support a dose-response relationship between breastfeeding duration and language skills and non-verbal intelligence during childhood and early adolescence.
Acta Paediatrica
Keywords: breastfeeding; cognitive development; dose-response relation; executive functions; language skills; non-verbal intelligence; Childhood and child development